Permanência na educação superior: contribuições da política de assistência estudantil do Instituto Federal de Educação, Ciência e Tecnologia da Paraíba – Campus Cabedelo - Carvalho, Evelin Sarmento de (2020)
The National Student Assistance Program - PNAES, instituted in 2010, provides for student assistance actions that support the permanence of students who have entered higher education through public inclusion policies and who are in situations of vulnerability. In this perspective, we analyzed the Student Assistance Policy of the Federal Institute of Education, Science and Technology of Paraíba - IFPB of the Campus of Cabedelo, in the view of students enrolled in higher education courses, regarding their contribution to academic permanence. To this end, we developed a study of an applied nature with a qualitative approach. For data collection, we applied a semi-structured questionnaire and conducted interviews with students from higher education courses in graphic design and biological sciences, participating in the student assistance policy. Then we treat the research data from the perspective of content analysis by BARDIN (2011), using as theoretical categories, in / exclusion and access and permanence, analyzing authors such as: Provin (2011), Veiga-Neto and Lopes (2011) , Zago (2006), Silva and Veloso (2013), Castelo Branco; Nakamura and Jezine (2016 and 2017) and others. We verified in our results, the profile change of the institution's students throughout its historical process; the contribution of the student assistance policy of the Campus of Cabedelo in the permanence of students with greater references to financial aid and mainly housing assistance; we also highlight the contribution of the posture and conduct of the teacher's figure in the students' permanence; and we also highlight the inexistence of actions with the purpose of pedagogical support for students of higher education during their academic trajectory. It was evident that the student assistance policy of the IFPB Campus de Cabedelo provides, predominantly, modalities of financial assistance as support to the students' permanence, prioritizing the attendance of their material demands, not being visible in the same proportion, strategies to attend to their demands symbolic, offering, for example, spaces for collective coexistence. At the end of the research, we propose, from the students' reports, an intervention project with the objective of building channels of dialogue with students to strengthen the feeling of belonging in the institution, promoting a systematic monitoring, thus contributing to permanence academic